Inflammatory biomarkers to predict adverse outcomes in postoperative patients with acute type A aortic dissection. (2nd January 2020) - Liu, Hua; Luo, Zhe; Liu, Lan; Yang, Xiaomei; Zhuang, Yamin; Tu, Guowei; Ma, Guoguang; Zhang, Ying; Zheng, Jili; Zhu, Duming; Wang, Chunsheng
Abstract: Objectives . The present study aimed to evaluate prognostic value of inflammatory markers for in-hospital mortality and renal complication in patients undergoing surgery for acute type A aortic dissection (ATAAD). Design . Serum concentration of C-reactive protein, leukocyte counts, procalcitonin (PCT), tumor necrosis factor (TNF)-α, interleukin-2 receptor (IL-2R), IL-6 and IL-8 were measured on the day of admission to the hospital (T0) and on 1st (T1), 2nd (T2), and 7th (T3) day after surgery. Results . 328 patients were included. There were significant differences between survivor group and non-survivor group in PCT, IL-2R, and IL-6 ( p = .001, p = .015, and p = .005). There were significant differences between patients with different AKI stage in PCT and IL-2R ( p = .001, p < .001). The area under receiver operating characteristics (ROC) curve on 30-day death was 0.686 for PCT, 0.718 for IL-2R, 0.694 for IL-6 and 0.627 for IL-8. The area under ROC curve on stage III AKI was 0.852 for PCT, 0.749 for IL-2R, 0.626 for IL-8, and 0.636 for TNF-α. IL-2 > 1438 U/ml and IL-6 > 45.5 pg/ml were independently associated with 30-day mortality ( p = .014 and p < .001). The area under ROC curve was 0.849 on score 2 (using 1 point for PCT > 4.58 ng/ml, 1 point for IL-2R > 1438 U/ml, 1 point for APACHE II score >15.5, and 1 point for IL-6 > 45.5 pg/ml). Conclusions . PCT and cytokines may be considered as predictors for adverse renal outcomes and mortality in patients with ATAAD patients after surgery. They are earlier than traditional biomarkers and combination of these biomarkers will improve the accuracy.